Globalization and Social Change: Gender-Specific Effects of Trade Liberalization in Indonesia. Issue Volume 66:Issues 4(2018) (December 2018) - Kis-Katos, Krisztina; Pieters, Janneke; Sparrow, Robert
Abstract We analyze the gender-specific effects of trade liberalization on participation in market work, domestic duties, and marriage rates in Indonesia. We show that female work participation increased and participation in domestic duties declined in regions that were more exposed to input tariff reductions. The effects of output tariff reductions were much less pronounced, and we find little impacts on men. Among the potential channels, we find that reductions in input tariffs led to a relative expansion of more female-intensive sectors as well as a decrease in sectoral gender segregation, especially among the low skilled. Liberalization also led to delayed marriage among both sexes and reduced fertility among less educated women.